2022
DOI: 10.1371/journal.pone.0268704
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among healthcare workers during COVID-19 pandemic in Thailand

Abstract: Objectives This study aimed to measure the prevalence of burnout syndrome, anxiety, depression, and post-traumatic disorders (PTSD), as well as examine their associated factors among Thai healthcare workers (HCWs) during COVID-19 outbreak. Method We employed a multiple-method design at a tertiary-care hospital in Bangkok between May 22, 2021 and June 30, 2021 by using an online survey. The information included demographic characteristics, work details, perceived support, PTSD symptoms, Maslach Burnout Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 53 publications
0
10
0
2
Order By: Relevance
“…Burnout was measured with the Maslach Burnout Inventory-General Survey (MBI-GS), translated and revised by Li Chaoping [21]. The scale includes three dimensions: emotional exhaustion, cynicism, and personal accomplishment.…”
Section: Burnoutmentioning
confidence: 99%
“…Burnout was measured with the Maslach Burnout Inventory-General Survey (MBI-GS), translated and revised by Li Chaoping [21]. The scale includes three dimensions: emotional exhaustion, cynicism, and personal accomplishment.…”
Section: Burnoutmentioning
confidence: 99%
“…During the height of the pandemic, however, resources to support nurses and other healthcare professionals in the delivery of patient care were under severe constraints [ 24 ]. As such, nurses in Thailand have experienced burnout, depression, and post-traumatic stress disorder [ 8 ] at rates similar to those documented in other countries [ 15 ]. However, to our knowledge, studies have yet to be conducted on nurse resilience and its relationships with nurse job outcomes in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…That study also reported increased sedentary behavior and undesirable weight gain. Thai healthcare workers also experienced negative mental health outcomes during the epidemic, such as burnout, anxiety, depression, and post-traumatic stress [ 14 ].…”
Section: Introductionmentioning
confidence: 99%